Analysis of E-Commerce System at Shopee Indonesia Company Using Strengths, Weaknesses, Opportunities, and Threats - Fatimah, Fatimah; Adinugraha, Hendri Hermawan (Journal of Education and Computer Applications, 2024)
This study intends to analyze Strengths, Weaknesses, Opportunities, and Threats (SWOT) on Shopee e-commerce in order to identify its advantages, disadvantages, opportunities, and threats. It has been noted by multiple studies that Shopee is the most popular e-commerce site in Indonesia, but practical experience in the field indicates that there are still a lot of complaints from customers regarding Shopee e-commerce. This research uses a qualitative descriptive approach by conducting a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). This research uses primary data obtained through observation. The data was obtained from direct observation using gadgets on the Shopee application. The ensuing data analysis shows that Shopee's reputation is its greatest asset, that it is not an Indonesian e-commerce company, that there are several rivals with comparable business models, and that there is a potential for a marketplace business that is not restricted by time or location. Based on these findings, Shopee may strengthen its opportunities and strengths while decreasing its threats and weaknesses by putting the S-O, W-O, S-T, and W-T strategies into practice. The S-O strategy contains opportunities that can be maximized. The W-O strategy contains a way out so that opportunities are not wasted. The S-T strategy contains how to respond to threats with the strengths possessed. The W-T strategy contains solutions to threats that may arise.